The Role of Muslims Rulers of the Subcontinent in the Promotion of Inter-Faith Harmony: A Study of Orientalistic Thought - Dr. Muhammad Riaz Mehmood; Dr. Ihsan Ur Rahman Ghouri (jihat-ul-islam, 2020)
All aspects of Islamic thought and philosophy are directly or indirectly concerned with the material and spiritual development of human beings. Humanitarianism and philanthropy have always been the primary goals of Muslims. That is why,Muslims have shown no hesitation in treating people of different religions kindly. Holy Prophet (peace and blessings of Allah be upon him) established full political and social relations with the people in Makkah, Madinah and other areas. He did not show any narrow mindedness in this regard. Muslims have always adhered to these golden principles of the Holy Prophet and tried their best to create an atmosphere of inter-faith harmony .The same issue of tolerance with nonMuslims was raised by Muslims in the subcontinent as well. Contrary to acknowledging these facts, some orientalists allege that the attitude of Muslim rulers in the subcontinent was cruel and bigoted towards non-Muslims. This research article analyzes the misconceptions of orientalists regarding forced preaching, protection of worship places, Jizyah and the conduct of Muslim conquerors.